2013
DOI: 10.1089/neu.2012.2696
|View full text |Cite
|
Sign up to set email alerts
|

Proton MR Spectroscopy Correlates Diffuse Axonal Abnormalities with Post-Concussive Symptoms in Mild Traumatic Brain Injury

Abstract: There are no established biomarkers for mild traumatic brain injury (mTBI), in part because post-concussive symptoms (PCS) are subjective and conventional imaging is typically unremarkable. To test whether diffuse axonal abnormalities quantified with three-dimensional (3D) proton magnetic resonance spectroscopic imaging (1 H-MRSI) correlated with patients' PCS, we retrospectively studied 26 mTBI patients (mean Glasgow Coma Scale [GCS] score of 14.7), 18-to 56-year-olds and 13 controls three to 55 days post-inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 20 publications
2
51
0
Order By: Relevance
“…Our findings within deep gray matter structures regarding NAA corroborate with our previous published results in which whole VOI analysis showed global gray matter NAA to be stable after mTBI. 18,19 The findings also agree with prior evidence showing that regional gray matter NAA, including thalamic NAA, is not decreased in patients after mTBI. 39 NAA reflects measures of neuronal integrity and metabolism.…”
Section: -1631-33supporting
confidence: 89%
See 2 more Smart Citations
“…Our findings within deep gray matter structures regarding NAA corroborate with our previous published results in which whole VOI analysis showed global gray matter NAA to be stable after mTBI. 18,19 The findings also agree with prior evidence showing that regional gray matter NAA, including thalamic NAA, is not decreased in patients after mTBI. 39 NAA reflects measures of neuronal integrity and metabolism.…”
Section: -1631-33supporting
confidence: 89%
“…Of note, we have previously reported global concentrations of N-acetylaspartate (NAA), choline (Cho), and creatine (Cr) in this patient cohort. 18,19 Thirteen healthy controls matched for sex, age, and handedness were also studied (5 women and 8 men, aged 33 6 11.6 years). Exclusion criteria used for controls were the same as for the patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are noteworthy in relation to other imaging modalities, such as diffusion imaging, task fMRI studies, and magnetic resonance spectroscopy, which have reported group differences between mTBI and healthy subjects 12,13,18,54 but limited success in discriminating individual patients. White matter studies of mTBI using diffusion imaging have shown fairly circumscribed anomalies in subdivisions of the corpus callosum, anterior corona radiata, SLF, and internal capsule.…”
Section: Bold Signals White Matter and Other Imaging Modalitiesmentioning
confidence: 54%
“…46 Since many individuals with mild TBI present damage to the frontal cortex 75 and those with PTHA present bilateral decreased levels of white matter N-acetyl aspartate (NAA) in the frontal and bilateral lobes indicative of axonal dysfunction, 76 such damage may contribute to the dysfunctional pain modulation found here, and hence the magnitude of CPTHA. Decreased level of NAA among individuals with postconcussive syndrome 77 may also support the aforementioned possibility.…”
Section: Cranial Sensitivity To Painmentioning
confidence: 67%